Kepastian Hukum terhadap Pembeli yang Beretikad Baik dalam Proses Balik Nama Sertipikat Tanah - Ahmadi Ahmadi; Risky Amelia (Wajah Hukum, 2025)
Land sale and purchase transactions that are not carried out through legal procedures according to statutory regulations are often used by the general public. The law in the area is not using a Sale and Purchase Deed made by a Land Deed Making Officer (PPAT) or Temporary PPAT (PPATS). This is often used by some people so that non-compliance with legal procedures results in the transfer of land rights not being able to be registered at the land office, so that the buyer does not obtain legal status as a legitimate land owner. Therefore, in this article, what will be reviewed is how the procedure so that the buyer can carry out a Change of Name according to the procedure and the legal impact if the transaction process is not carried out correctly. Normative and empirical Juridical Methods, namely by emphasizing secondary data by studying and reviewing the principles of positive law derived from library data and legal comparisons, as well as elements or factors related to the research object as part of field research. Underhand transfer of rights transactions in this case there is a defect or flaw, however, the buyer is considered to have good intentions by checking and taking care of the validity of the documents owned, therefore the change of name can be carried out based on an authentic letter made by a non-PPAT in this case a Court Decision that has permanent legal force. In this case, the Community is considered to be more careful, thorough and careful regarding the land object and can check the history of the land at the BPN.